PERLINDUNGAN HAK TAGIH KREDITOR DENGAN JAMINNAN HAK ATAS TANAH BERBENTUK NOTARIS - Aryanto, Dafa; Sufiarina; Marbun, MT; Tihadanah (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2024)
Article 1131 of the Indonesian Civil Code stipulates a general guarantee on the property rights of all debtors. Meanwhile, Article 1132 refers to a specific guarantee directed only at certain properties. For instance, suppose a debtor provides collateral for debt repayment by designating a specific piece of land in a notarial deed. In this case, it is essential to examine the legal status of the creditor who accepts the guarantee, as well as the legal protections available to the creditor if the debtor fails to repay the debt as agreed. This research aims to examine the legal standing of creditors who accept land guarantees in the form of a notarial deed as well as to comprehend the legal protections available to creditors when the debtor fails to repay the debt as agreed and the protective measures or actions creditors can initiate. To achieve this objective, a normative juridical research methodology was adopted with a legislative approach, focusing on the rules regarding property guarantees and the regulation of land mortgage rights as collateral. The obtained results shows that the designation of specific land in a notarial deed as collateral for debt repayment did not provide preferential rights to the creditor. Following the findings of this investigation, it is recommended that the guarantee of land rights be formalized through a deed of encumbrance on land rights executed by the Land Deeds Official (PPAT). However, in the absence of a voluntary resolution, the creditor can only protect claimed rights by filing a breach-of-contract lawsuit.